Hydrogen-Deuterium Exchange Mass Spectrometry of Membrane Proteins in Lipid Nanodiscs - Redhair, Michelle (Chem Phys Lipids, 2019)
Hydrogen deuterium exchange mass spectrometry (H/DX MS) provides a quantitative comparison of the relative rates of exchange of amide protons for solvent deuterons. In turn, the rate of amide exchange depends on a complex combination of the stability of local secondary structure, solvent accessibility, and dynamics. H/DX MS has, therefore, been widely used to probe structure and function of soluble proteins, but its application to membrane proteins was limited previously to detergent solubilized samples. The large excess of lipids from model membranes, or from membrane fractions derived from in vivo samples, presents challenges with mass spectrometry. The lipid nanodisc platform, consisting of apolipoprotein A-derived membrane scaffold proteins, provides a native like membrane environment in which to capture analyte membrane proteins with a well defined, and low, ratio of lipid to protein. Membrane proteins in lipid nanodiscs are amenable to H/DX MS, and this is expected to lead to a rapid increase in the number of membrane proteins subjected to this analysis. Here we review the few literature examples of the application of H/DX MS to membrane proteins in nanodiscs. The incremental improvements in the experimental workflow of the H/DX MS are described and potential applications of this approach to study membrane proteins are described.